Electrochemical Sensors Based on Covalent Organic Frameworks: A Critical Review - Chen, Sidi; Yuan, Baiqing; Liu, Gang; Zhang, Daojun (Frontiers in Chemistry, 2020)
The metal-free cousins of metal-organic frameworks, covalent organic frameworks (COFs), are a class of predesignable crystalline polymers composed of light elements and connected by strong covalent bonds. COFs are being paid more and more attention in electrochemical sensors due to their fascinating properties, such as highly tunable porosity, intrinsic chemical and thermal stability, structural diversity, large specific surface area, and unique adsorption characteristics. However, there are still some key issues regarding COFs to be urgently resolved before they can be effectively applied in electrochemical sensing. In this review, we summarized recent achievements in developing novel electrochemical sensors based on COFs, and discussed the key fundamental and challenging issues that need to be addressed, including the mechanisms underlying charge transport, methods to improve electrical conductivity, immobilization methods on different substrates, synthesis strategies for nanoscale COFs, and application of COFs in different fields. Finally, the challenges and outlooks in this promising field are tentatively proposed.